2020
DOI: 10.1371/journal.pone.0237252
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus prevalence and vaccine antibody titers in children HIV exposed but uninfected in Botswana

Abstract: Background Botswana introduced the HBV vaccine at birth for all newborns in 2000. To the best of our knowledge, since the introduction of HBV vaccination, there have been limited data for vaccine response to HBV and its impact on early childhood HBV infections among children HIV exposed but uninfected in Botswana. Aims To determine the prevalence of hepatitis B surface antigen (HBsAg) and HBV vaccine response in 18 months old children HIV exposed but uninfected in Botswana. Methods Stored plasma samples from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…This result is probably due to methods of preventing mother-to-child transmission of HIV implemented in the country. It has been described in Botswana where they observed a high response to the HBV vaccine among children exposed to HIV but uninfected [8]. Open Journal of Gastroenterology Concerning children from women infected by HVB, we did not observe a difference in anti-HBs levels with those with non-infected women.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This result is probably due to methods of preventing mother-to-child transmission of HIV implemented in the country. It has been described in Botswana where they observed a high response to the HBV vaccine among children exposed to HIV but uninfected [8]. Open Journal of Gastroenterology Concerning children from women infected by HVB, we did not observe a difference in anti-HBs levels with those with non-infected women.…”
Section: Discussioncontrasting
confidence: 49%
“…Some factors may negatively affect the immunization and the child will risk an infection despite the vaccine administration. Among these factors, in literature we have: a hepatitis B infection in the mother [7], the poor nutritional status [8], an HIV infection of the child [9], the low number of doses [10], the poor type of vaccine [11], and the male sex of the child [3]. In SSA, problems associated with conservation and cold chain of these vaccines could also affect their efficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…50 In a recent study to investigate HBV vaccine responses in HIV-exposed but uninfected children in Botswana, a 98.9% protective immunity was reported in this cohort by 18 months of age and only 75% had received the timely birth dose. 21 Decline in immunity from vaccination has been reported from Malawi and South Africa in adolescence leading to an increased risk of acquisition of HBV infection because of sexual activity or injecting drug use. 2,51 Vaccine failures also have been reported as a result of development of escape mutants.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recent study reported a 1.74% prevalence rate of HBsAg in HIV-infected mothers at the time of delivery, who were on treatment with zidovudine (ZDV) and lamivudine (3TC) or tenofovir (TDF) and emtricitabine (FTC) containing antiretroviral treatment ART regimens, which also have anti-HBV (antibody to hepatitis B virus) activity. 21 Occult hepatitis B virus infection (OBI) was observed in 6.6% of HBsAg-negative women. 19 There is paucity of data on the prevalence of viral hepatitis in patients with features of liver disease in Botswana.…”
Section: Read Onlinementioning
confidence: 99%